Visual Outcomes in Experimental Rodent Models of Blast-Mediated Traumatic Brain Injury - Evans, Lucy P.; Roghair, Ariel M.; Gilkes, Noah J.; Bassuk, Alexander G. (Frontiers in Molecular Neuroscience, 2021)
Blast-mediated traumatic brain injuries (bTBI) cause long-lasting physical, cognitive, and psychological disorders, including persistent visual impairment. No known therapies are currently utilized in humans to lessen the lingering and often serious symptoms. With TBI mortality decreasing due to advancements in medical and protective technologies, there is growing interest in understanding the pathology of visual dysfunction after bTBI. However, this is complicated by numerous variables, e.g., injury location, severity, and head and body shielding. This review summarizes the visual outcomes observed by various, current experimental rodent models of bTBI, and identifies data showing that bTBI activates inflammatory and apoptotic signaling leading to visual dysfunction. Pharmacologic treatments blocking inflammation and cell death pathways reported to alleviate visual deficits in post-bTBI animal models are discussed. Notably, techniques for assessing bTBI outcomes across exposure paradigms differed widely, so we urge future studies to compare multiple models of blast injury, to allow data to be directly compared.